Pengaruh Kompetensi Kepribadian Guru PAK Terhadap Tingkah Laku Siswa Kelas VII SMP Negeri 3 Tapian Nauli Tahun Pembelajaran 2022/2023 - Yemima Esterina Sipahutar; Pestaria Naibaho; Nurelni Limbong (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the magnitude of the influence of the personality competence of Christian Religious Education teachers on the behavior of class VII students at SMP Negeri 3 Tapian Nauli for the 2022/2023 academic year. The method used in this research is a quantitative research method. The population is all students in class VII of SMP Negeri 3 Tapian Nauli for the 2022/2023 academic year who are Christians, totaling 35 people. Data was collected using a positive closed questionnaire with 55 items, namely 35 items for variable 2022/2023: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.578 > rtable(a=0.05,n=35) = 0.334. b) Testing a significant relationship obtained tcount= 4.071 > ttable(a=0.05,dk=n-2=33)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="25.25"+0.37X. b) Regression coefficient of determination test (r2) = 33.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=22, dk denominator=n-2=35-2=33) namely 16.54 > 1.62. Thus Ha is accepted and H0 is rejected.